REVISITING KRASHEN’S SLA THEORY THROUGH MODERN PSYCHOLINGUISTICS - Elvi Mastawiyah (UIN Sumatera Utara, 2025)
This paper aims to critically examine Stephen Krashen's theory of language acquisition within the context of modern psycholinguistics. The approach used is a critical theoretical review, comparing Krashen's five main hypotheses with recent findings in neurolinguistics and cognitive science. The main criticisms of this theory lie in its empirical limitations, methodological weaknesses, and lack of integration with contemporary neurocognitive evidence. Nevertheless, this review confirms Krashen's important contribution as a foundation for the study of second language acquisition, while emphasizing the need to update the concepts of input and language acquisition processes to align with a more empirically evidence-based psycholinguistic approach.